Anagrelide for platelet-directed cytoreduction in polycythemia vera: Insights into utility and safety outcomes from a large multi-center database. (August 2022) - Rippel, Noa; Tremblay, Douglas; Zubizarreta, Nicole; Podoltsev, Nikolai; Gotlib, Jason; Heaney, Mark; Kuykendall, Andrew; O'Connell, Casey; Shammo, Jamile M.; Fleischman, Angela; Kremyanskaya, Marina; Hoffman, Ronald; et al.
Abstract: Anagrelide (ANA) is a platelet-specific cytoreductive agent utilized in the guideline-directed management of high-risk essential thrombocythemia. In the context of polycythemia vera (PV), ANA is occasionally employed in clinical practice, although data has not consistently demonstrated a benefit to targeting a platelet goal as a therapeutic endpoint. The aim of the current study was to delineate the patterns of ANA use in PV, and to describe outcomes and toxicities. Within a multi-center cohort of 527 patients with PV, 48 received ANA (9 excluded for absent data). 27 (69.2%) had high-risk PV, 10 (25.6%) had prior thrombosis, and none had extreme thrombocytosis, acquired von Willebrand disease, and/or documented resistance to hydroxyurea. While ANA effectively lowered median platelet count, 43.5% of patients had an unresolved thrombocytosis at time of ANA discontinuation. Treatment-emergent adverse events—including headaches, cardiac palpitations and arrhythmias, nausea, vomiting and/or diarrhea—led to ANA discontinuation in 76.9% of patients. Further, three patients experienced arterial thromboses during a median duration of 27.5 months of ANA therapy. In conclusion, this study highlights ANA's restrictive tolerability profile which, compounded by the absence of clear advantage to strict platelet control in PV, suggests the use of ANA should be limited in this setting. Highlights: Literature has not shown clear benefit to platelet control in polycythemia vera (PV). Anagrelide (ANA) is occasionally used in PV, although not part of current guidelines. ANA is effective at selectively reducing platelet counts in patients with PV. ANA use in PV demonstrates a restrictive treatment-emergent adverse event profile. ANA use in PV is not uniformly associated with thrombosis freedom.